Ensuring human rights in the Constitution, laws, and other normative acts. - Abdusalomov Mirabbos; Muzaffarov Ikromjon Nodirbek ogli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, by reflecting human rights and freedoms in our Constitution, we will be able to see information about the rights and freedoms of citizens in the performance of these rights and timely fulfillment of their obligations, to go to court against government agencies and officials.